Analisis Ekonomis Sewa atau Beli Alat Excavator pada Kegiatan Produksi Bijih Timah PT Prima Timah Utama, Desa Cit, Kabupaten Bangka - Randa Wirana; Irvani Irvani; Mardiah Mardiah (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2021)
Fulfilling the annual production target of PT Prima Timah Utama based on the 2019 Work Plan and Budget of 1,100,000 m3 requires the procurement of adequate mining equipment both in terms of quantity and production capacity, especially excavators. The equipment procurement plan is estimated by calculating the need for tools using a sample of 30 distribution time data, 9-time constraints data, and some supporting calculation data that results in tool requirements. The cost of ownership of the equipment to be compared with the rental cost is obtained from the purchase price, interest, residual value and economic life of the equipment, the cost comparison is then analyzed using the Net Present Value method. The calculation results show that PT Prima Timah Utama must add 2 units of CAT 320D2 excavator for overburden stripping and wash with an estimated equipment cost of Rp. 2,224,076,433.6 for 2 units of new equipment and Rp. 2,541,131,520 for 2 units of rental equipment where the difference between the rental and purchase equipment is Rp. 317,055,086.4 for one year of work. The result of the analysis with the evaluation of NPV investment has a value of Rp. 32,313,773,567.7 or >0 which states that the investment is declared feasible.